Solutions to Promote Startup for the Youth in Minoritty and Moutainous Region of Thai Nguyen Province - Vietnam - NAM, VU QUYNH; HUY, DINH TRAN NGOC (The journal of contemporary issues in business and government, 2021)
Since startup has been becoming hot issue in many Vietnam universities and communities in recent years, we performed this study relating startup in minorities in such cities as Thai Nguyen city in the North of Vietnam. By using mainly qualitative analysis, analytical, synthesis and inductive methods, this study specified that it is better to train and equip young people with startup experiences through mass media and through local youth union activities because they may lack of experiences. Next, it is necessary to train and propagate about the experiences of some young startup models in the area; set up startup groups and clubs at all levels, from commune / ward levels to support young people with startup knowledge for each specific field. Finally, our study also propose conclusion with recommendations for startups.